How Perception Affects Racial Categorization: On the Influence of Initial Visual Exposure on Labelling People as Diverse Individuals or Racial Subjects. (January 2015) - Harsányi, Géza; Carbon, Claus-Christian
In research on racial categorization we tend to focus on socialization, on environmental influences, and on social factors. One important factor, though, is perception itself. In our experiment we let people label persons on dimensions which they could freely use. The participants were initially exposed to a full series either of black faces or of white faces. We observed a clear effect of initial exposure on explicit verbal categorizations. When initially exposed to white faces, participants used racial labels for the subsequent black faces only. In contrast, racial labels were used for black as well as white faces after initial exposure to black faces, which indicates a shift to in-group categorization after having initially inspected black faces. In conclusion, this effect documents highly adaptive categorizations caused by visual context alone, suggesting that racial thoughts are based on relatively volatile category representations.